Going beyond cognitive approach to behavioral stream in economic sciences: Behavioristic and evolutionary perspectives - Korzeniowska, Dominika; Sułkowski, Łukasz (Journal of Entrepreneurship, Management and Innovation, 2020)
The paper is a proposal of the triangulation of a theory basis for the behavioral stream in economic sciences that currently mostly uses a cognitive approach, by adopting a behavioristic and evolutionary perspective into that scope of reflection. A narrative literature review of scientific databases by means of Internet search engines based on the combinations of relevant keywords was used. The final selection included 37 articles and 21 monographs subjected to further analysis. The analysis showed that by adopting other perspectives than just a cognitive one into behavioral economics research can enrich theoretical and empirical foundations, provide new research tools, and enable discoveries on human economic behaviors. Evolutionary concepts also seem to gain in importance nowadays, especially in terms of neuroscientific methods used to investigate how the human brain functions. The combination of all three approaches seems quite promising and worth further development, as it may lead to not only uncovering the mechanisms underlying economic behaviors but also may help people to make better decisions. Thanks to the combination of the three approaches (paradigms) pictured together (which has not previously been present in the literature on the subject), the paper aims to inspire behavioral economic researchers to search for the theoretical basis of their scientific quest going beyond the cognitive canon, to facilitate embedding their studies in a proper paradigm or finding the relevant concept/theory, and also recognizing niche or complementary research areas. Therefore, the article adds to a discussion on the theoretical foundations of the stream and the process of shaping its scientific identity.